2020
DOI: 10.1093/tbm/ibaa115
|View full text |Cite
|
Sign up to set email alerts
|

Clinical management of emotions in patients with cancer: introducing the approach “emotional support and case finding”

Abstract: The current approach to the management of emotions in patients with cancer is “distress screening and referral for the provision of psychosocial care.” Although this approach may have certain beneficial effects, screening and referral programs have shown a limited effect on patient psychological well-being. We argue that this limited effect is due to a mismatch between patient needs and the provision of care, and that a fundamental reconceptualization of the clinical management of emotions in patients with can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 58 publications
(13 reference statements)
0
27
0
2
Order By: Relevance
“…These challenges include considering their obligations to patient autonomy while deciding how much information needs to be provided, and how much patients want to know from the caregivers. In addition, caregivers sometimes find it difficult to convey such information in a realistic way, but also keep the patient hopeful [8,11]. In an Australian study involving 126 patients diagnosed with incurable cancer, 59% were curious about the expected survival when first diagnosed; 34 and 40% wanted to be asked about when they would rather discuss expected survival and death, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These challenges include considering their obligations to patient autonomy while deciding how much information needs to be provided, and how much patients want to know from the caregivers. In addition, caregivers sometimes find it difficult to convey such information in a realistic way, but also keep the patient hopeful [8,11]. In an Australian study involving 126 patients diagnosed with incurable cancer, 59% were curious about the expected survival when first diagnosed; 34 and 40% wanted to be asked about when they would rather discuss expected survival and death, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…It is hoped that with increased ability, volunteers will be able to develop their skills as the closest companions of patients in overcoming situations that change according to the circumstances of their disease or when facing rejection, lack of acceptance of their diagnosis, poor prognosis, news of death and sadness, lack of knowledge of medical science, distrust, and family-related resistance to open communication about cancer diagnosis and prognosis [17,18]. So it is expected that volunteers when meeting with patients are expected to be able to conduct motivational interviews and integrative therapy while using communication strategies such as empathic listening, being an active listener, normalizing, refraining, reflecting, validating, using hopeful language, and other therapeutic techniques including breathing exercises, behavioral interventions, decision balance, existential strategies, hereand-now, relaxation, visual techniques, written techniques, and psychoeducation when treating cancer patients [11,16,19]. Palliative care can offer high-value alternatives in care of advanced cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…These indicators can be found in various research areas, including emotional dynamics [32], emotion regulation [33], life goals, and subjective wellbeing [34], as well as the network theory on mental disorders [35]. In the field of psycho-oncology, distinguishing between adaptive and maladaptive emotions is a rather novel concept [12,36]. The dominant opinion at present is that intense emotions need to be treated [37].…”
Section: Discussionmentioning
confidence: 99%
“…Several screening instruments have been developed to help identify patients likely to require professional mental health care, one example being the Distress Thermometer [8]. However, it has been consistently observed that the majority of patients scoring above the cutoff for distress subsequently decline professional mental health care [9][10][11][12]. Typically, while over 30-40% of patients score above the cutoff for distress [12,13], only around 10-15% of patients report a need for professional mental health care [7,12,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation